2013
DOI: 10.1007/s00228-013-1541-5
|View full text |Cite
|
Sign up to set email alerts
|

Preladenant, a selective adenosine A2A receptor antagonist, is not associated with QT/QTc prolongation

Abstract: At clinical and supratherapeutic doses, preladenant is not associated with QTc prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Finally, istradefylline and tozadenant, A 2A -AR antagonists, are new compounds used in patients to treat Morbus Parkinson (Hauser et al, 2014; Schapira et al, 2014; Adams et al, 2015). Their potential cardiac side effects have been partially studied in healthy volunteers (Wang et al, 2013). Other A 2A -AR antagonists have been studied clinically for treatment of melanoma (Adams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, istradefylline and tozadenant, A 2A -AR antagonists, are new compounds used in patients to treat Morbus Parkinson (Hauser et al, 2014; Schapira et al, 2014; Adams et al, 2015). Their potential cardiac side effects have been partially studied in healthy volunteers (Wang et al, 2013). Other A 2A -AR antagonists have been studied clinically for treatment of melanoma (Adams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…266 A transient increase in systolic and diastolic blood pressure occurred after SCH420814 treatment, not associated with a delay of cardiac repolarization. 267 Preladenant showed good dose-dependent efficacy in vivo in the haloperidolinduced rat catalepsy assay and reversed the rat hypolocomotion induced by A 2A agonists. 28 Early clinical trials have been performed in PD patients where SCH420814, as mono-therapy or added to L-DOPA therapy, produced an improvement in motor function and a sustained efficacy in improving on-time and reducing off-time.…”
Section: Therapeutic Applications Of a 2a Antagonists In Clinical Trialsmentioning
confidence: 92%
“…Preclinical studies performed in different animal models reported a good safety profile and tolerability at different doses . A transient increase in systolic and diastolic blood pressure occurred after SCH420814 treatment, not associated with a delay of cardiac repolarization . Preladenant showed good dose‐dependent efficacy in vivo in the haloperidol‐induced rat catalepsy assay and reversed the rat hypolocomotion induced by A 2A agonists .…”
Section: Therapeutic Applications Of A2a Antagonists In Clinical Trialsmentioning
confidence: 96%